FACTORS INFLUENCING SELF-CARE BEHAVIORS AMONG TYPE 2 DIABETES PATIENTS WITH GOOD GLYCEMIC CONTROL IN KHLONG LUANG DISTRICT, PATHUM THANI PROVINCE - Klongkhoy, Puttarawadee; Sillaparassamee, Ratthapol; Nakkliang, Kanittha (Journal of Public Health and Innovation, 2026)
This cross-sectional study examined self-care behaviors and factors associated with self-care behaviors among patients with type 2 diabetes who achieved good glycemic control in Khlong Luang District, Pathum Thani Province. The sample consisted of 261 patients aged 20 years and above with a fasting blood glucose level of no more than 140 mg/dL or an HbA1c level of no more than 7%. Participants were selected using multistage random sampling. Data were collected using a questionnaire covering personal characteristics, health literacy, social support, and self-care behaviors. Data were analyzed using descriptive statistics, Pearson’s correlation coefficient, and stepwise multiple regression analysis. Statistical significance was set at 0.05. The results showed that overall self-care behaviers of controlled type 2 diabetes mellitus patients was at high level ( = 30.72, SD = 3.83). Factors significantly affecting self-care behavior of type / diabetes patients at p=0.05 level included health literacy (B = 0.430, β = 0.265, p = 0.001) and Social support (B = 0.662, β = 0.219, p = 0.003) These variables collectively accounted for 12.22% of the variance in self-care behaviors among type 2 diabetes patients with good glycemic control (R2 = 0.122). Consequently, health literacy and social support play a crucial role in self-care behaviors. Relevant local agencies can utilize these findings as a guideline to plan and design health literacy enhancement programs. Furthermore, they should promote initiatives driven by family, community, and multidisciplinary team support to foster appropriate self-care behaviors among patients with diabetes.